0
$\begingroup$

This is a question relating to SL Loney's coordinate geometry book (article 56).

We have $Ax + By + C = 0$ as the general form of a line.

Want to arrive at $xcos(\alpha)+ ysin(\alpha) - p = 0$ as the 'normal form'

So we have the equations represent the same line thus we have the common ratios of coefficients

$ cos(\alpha)\over A$ =$ sin(\alpha)\over B$ =$ -p\over c$

Now here is where I can't arrive myself.

$ p\over c$ = $ cos(\alpha)\over -A$ = $ sin(\alpha)\over -B$ = $ \sqrt{cos^2(\alpha) + sin^2(\alpha) \over A^2 + B^2}$ = $ 1 \over \sqrt{A^2 + B^2}$

Ultimately, I'm hoping someone can shed some light on how he arrived at the $ \sqrt{cos^2(\alpha) + sin^2(\alpha) \over A^2 + B^2}$ part...

$\endgroup$
  • $\begingroup$ thanks all for the insight, very much appreciated. $\endgroup$ – saul Nov 19 '14 at 7:13
0
$\begingroup$

$$\frac{p}{c}=\frac{cos\alpha}{-A}=\frac{sin\alpha}{-B}=n$$ let's take each term apart:

$$\frac{cos\alpha}{-A}=n ==> -An=cos\alpha$$ $$\frac{sin\alpha}{-B}=n ==> -Bn=sin\alpha$$

Now square both sides :

$$A^2n^2=cos^2\alpha$$ $$B^2n^2=sin^2\alpha$$

Now add them up :

$A^2n^2 + B^2n^2 = sin^2\alpha+cos^2\alpha$

$n^2(A^2+B^2)=1$

$n^2=\frac{1}{A^2+B^2}$

$n=\sqrt{\frac{1}{A^2+B^2}}$

So you can say:

$$\frac{p}{c}=\frac{cos\alpha}{-A}=\frac{sin\alpha}{-B}=\sqrt{\frac{1}{A^2+B^2}}$$

$\endgroup$
0
$\begingroup$

If $\dfrac p c = \dfrac{\cos(\alpha)}{-A } = \dfrac{ \sin(\alpha)}{ -B}=k$

$$1=\cos^2\alpha+\sin^2\alpha=k^2(A^2+B^2)\implies k^2=?$$

$\endgroup$
0
$\begingroup$

So, we have a line represented by an equation: $Ax + By + C = 0$. To get the equation of this form we need to multiply the $x \sin \alpha + y \cos \alpha + r = 0$ form by some koefficient $\mu$. Now, lets find the $\mu$:

$\mu \cdot A x + \mu \cdot B y + \mu \cdot C = x \cos \alpha + y \sin \alpha + r;$

from which(because x and y are separate axises):

$\mu \cdot A = \cos \alpha$

and

$\mu \cdot B = \sin \alpha$

from which

$(\mu \cdot A)^2 + (\mu \cdot B)^2 = (\cos \alpha)^2 + (\sin \alpha)^2$ => $\mu^2 (A^2+B^2) = 1$ => $\mu = \sqrt{\frac{1}{A^{2} + B^{2}}}$;

also, $C = \frac{r}{\mu}$ => $\mu = \frac{r}{C}$;

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.